The genome sequence of the dun-bar pinion, Cosmia trapezina (Linnaeus, 1758) - Boyes, D; Godfray, C; Holland, PWH (F1000 Research Ltd, 2022)
We present a genome assembly from an individual male Cosmia trapezina (dun-bar pinion; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 825 megabases in span. The majority of the assembly (99.87%) is scaffolded into 32 chromosomal pseudomolecules with the Z chromosome assembled. The complete mitochondrial genome was also assembled and is 15.4 kilobases in length.